2018
DOI: 10.1177/0890334418812069
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Expression After Domperidone Treatment in Postpartum Women: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Insufficient milk production is among the most cited reasons by mothers for discontinuing breastfeeding. Medications that can increase milk production, such as domperidone, an off-label galactagogue, are often prescribed. Domperidone is controversial as it is not approved for any purpose in the United States and is approved only for gastrokinetic purposes in Canada and other countries. Research aim: The aim was to update the existing literature on the efficacy of domperidone as a galactagogue compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The current findings are consistent with previous meta-analysis using domperidone to significantly increase human milk volume 17,18 . This consistence could be owing to the mechanism of domperidone, which is a dopamine antagonist that can enhance milk volume through stimulating prolactin release 5 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current findings are consistent with previous meta-analysis using domperidone to significantly increase human milk volume 17,18 . This consistence could be owing to the mechanism of domperidone, which is a dopamine antagonist that can enhance milk volume through stimulating prolactin release 5 .…”
Section: Discussionsupporting
confidence: 92%
“…Risk ratio (RR) was utilized for dichotomous variables, and mean difference (MD) for continuous variables. Formulas used to calculate the changes in human milk volume were adopted from the previous review evaluating the efficacy of domperidone on milk production 18 . Summary measures were presented using effect size with 95% confidence intervals (CI).…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent systematic reviews and meta-analyses have demonstrated domperidone to be more effective than a placebo in improving breast milk volume in mothers of preterm infants [13,14], but evidence remains inconclusive outside of this setting [4]. There also remain uncertainties regarding the population that would most benefit from this treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 meta-analysis of seven randomized controlled trials (RCTs; N=371) evaluated the effectiveness of domperidone in increasing milk supply in lactating mothers with insufficient production. 1 It should be noted that domperidone is not approved by the Food and Drug Administration for use in the United States and using it as a galactagogue is an off-label use of the drug. Patients were postpartum mothers 18 to 35 years old who were not producing a sufficient milk supply for their infants.…”
mentioning
confidence: 99%